2017
DOI: 10.3390/ijerph14030312
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-Related Air Pollution and Childhood Asthma: Recent Advances and Remaining Gaps in the Exposure Assessment Methods

Abstract: Background: Current levels of traffic-related air pollution (TRAP) are associated with the development of childhood asthma, although some inconsistencies and heterogeneity remain. An important part of the uncertainty in studies of TRAP-associated asthma originates from uncertainties in the TRAP exposure assessment and assignment methods. In this work, we aim to systematically review the exposure assessment methods used in the epidemiology of TRAP and childhood asthma, highlight recent advances, remaining resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 94 publications
(167 reference statements)
0
26
1
Order By: Relevance
“…A growing number of studies suggest that dwelling environment, lifestyles and indoor air pollution contribute to the development of allergic disease [ 10 ]. Recent meta-analysis [ 11 , 12 ] concluded that living or attending schools near high traffic density roads with higher levels of motor vehicle air pollutants increased the incidence and prevalence of childhood asthma. Sun et al [ 13 ] declared that the lifestyle and home environment exposure undergone by children between 1–8 years are important asthma and allergy risk factors in Northeast Texas.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies suggest that dwelling environment, lifestyles and indoor air pollution contribute to the development of allergic disease [ 10 ]. Recent meta-analysis [ 11 , 12 ] concluded that living or attending schools near high traffic density roads with higher levels of motor vehicle air pollutants increased the incidence and prevalence of childhood asthma. Sun et al [ 13 ] declared that the lifestyle and home environment exposure undergone by children between 1–8 years are important asthma and allergy risk factors in Northeast Texas.…”
Section: Introductionmentioning
confidence: 99%
“…Ambient air pollutants, including NO 2 , PM 2.5 , PM 10 , BC, and BTEX, have been shown to exacerbate asthma [6][7][8][9]16,19,20,22,23,25,51,52]. Although Calgary has relatively good air quality [39], this study shows that significant correlations exist between ambient pollutants and AEVRs, though there is seasonal variation.…”
Section: Discussionmentioning
confidence: 78%
“…Traffic-related air pollutants (TRAP), notably nitrogen dioxide (NO 2 ) and particulate matter with a diameter less than 2.5 micrometers (PM 2.5 ), have been widely researched and are known to both exacerbate asthma and lead to decreased lung function, increased risk of asthma onset, and increased asthma-related hospitalizations [8,9,[16][17][18][19][20][21]. Many studies have noted that consistent exposure to elevated levels of NO 2 and PM 2.5 can decrease lung function and lead to asthmatic symptoms such as wheezing through airway inflammation and oxidative stress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hankey S et al 2016 [21] combined facility-demand and LUR models to highlight exposure patterns during active travel suggesting that it should be possible to reduce exposure by~15% after intervening on the given scenario. Recently, several studies confirmed that the health benefits linked to active travel outweigh the risks such as exposure to air pollution or accidents, suggesting that the attempt to build more walkable and bikeable urban environments is worth the effort [22][23][24].…”
Section: Introductionmentioning
confidence: 99%